PRINCIPAIS FATORES DA EVASÃO EM CURSOS SUPERIORES PRESENCIAIS NA ÁREA DE CIÊNCIAS SOCIAIS APLICADAS: ESTUDO DE CASO EM UMA INSTITUIÇÃO DE ENSINO SUPERIOR PARTICULAR DE PEQUENO PORTE - SOUZA , MAURÍCIO LOPES DE (2016)
One of the mainly challenges encountered while managing Higher Education Institutions are the consequences caused by students desertion. It is a problem that results in discomfort and preoccupation about the organization sustainability. The consequences of school evasion increase are causing damages not only to the education, but also to the future of a Nation. The present work looks for the identification of the students characteristics, not only of those who dropped out of school, but also of the newly graduated, trying to comprehend the influencing factors that support the students decisions of deserting or finishing the graduation course, and also comprehend the strategies used by the researched institution. For this purpose the mainly approaches were considered about the concepts of desertion, various ways of its calculation used by Higher Education Institutions and its most common causes. This work primary focus is to obtain a deeper knowledge about student desertion to give background to new studies that could help in preventing school dropouts. It is about a case study considering a private school small-sized located in the interior of the State of Sao Paulo and its higher education in-person courses of bachelor and technology degree in Social Sciences. The survey was conducted with structured questionnaires applied to dropout students and students who got their degree, both between 2012 and 2015, and structured interviews with managers, teachers and recent dropout students. The results have showed similarity among students with small differences between the group of desertion causes of each one. Keywords: